Causal attributions for poverty in citizens of Córdoba (Argentina): Psychometric analysis using CTT and IRT - Reyna, Cecilia (2024)
The tripartite model proposed by Feagin (1972) is widely used, although empirical evidence does not always support it. Thus, we set out to obtain empirical evidence on the psychometric properties of a pool of items on causes of poverty using CTT and IRT. In this research/study, 280 citizens of Córdoba from 18 to 65 years old participated. Results from confirmatory factor analysis and internal consistency showed acceptable values for the three-factor models. Results derived from IRT indicate that, in general, the items estimate a wide range of values of the latent traits, discriminating between people with different levels of trait. The need to gather new empirical evidence of Feagin’s proposal using complementary methods is highlighted.